Screening for nasopharyngeal carcinoma in high-incidence regions——Next steps - Allan Hildesheim (Guangxi Yike Daxue xuebao)
Epstein-Barr virus (EBV) infection is a well-established risk factor in the development of nonkeratinizing and undifferentiated forms of nasopharyngeal carcinoma (NPC) common in parts of China and Southeast Asia. Early detection of NPC can significantly improve survival rates, as the 5-year survival rate for patients diagnosed at an early stage can exceed 90% after treatment. Studies have demonstrated that screening for NPC using EBV markers is an effective tool for identifying individuals with the disease. Future efforts should focus on implementing screening programs in high-incidence populations, assessing and refining screening algorithms, and exploring new, potentially more cost-effective screening methods. It is crucial to ensure that any new approaches are validated as superior or non-inferior to existing protocol before being adopted on a wider scale. The success of these screening tools in reducing NPC-related morbidity and mortality will depend on their effective implementation and ensuring access for the populations most in need of preventive interventions. This opinion piece briefly summarizes the current evidence supporting EBV-based screening for NPC detection and discusses future steps, including: 1) the implementation of effective NPC screening programs, 2) the evaluation of improvements in screening methodologies, and 3) the consideration of novel approaches to screening.